The effect of game-based learning on backward rolling skills in children aged 11–12 years: an experimental study - Sri Gusti Handayani; Anton Komaini; Weny Sasmitha; Heru Andika (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
Backward roll ability remains a major obstacle in gymnastics learning for children aged 11-12 years. Difficulty performing this movement stems from limited coordination, physical strength, and fear. This situation highlights the need for learning innovations that can increase children's engagement and motivation. One potential solution is the use of a Game-Based Learning approach, a learning model that integrates game elements into the movement learning process. This study aims to analyze the effect of game-based learning on backward roll ability in children aged 11-12 years. This study used a quasi-experimental research design with a posttest-only control design. Participants consisted of elementary school children divided into an experimental group and a control group. Data were collected using a gymnastics ability assessment instrument and analyzed using descriptive statistics and an independent sample t-test. The results showed that children in the experimental group performed better than those in the control group. These findings suggest that game-based learning can increase children's engagement and provide a more effective and enjoyable movement learning experience. This approach has the potential to be an innovative strategy to improve the quality of gymnastics learning in elementary schools.